Kinematics Analysis and Dynamic Simulation of the Crank-group Driving Mechanism - Wang Yuqi; Liu Shoufa; Cao Jujiang (Jixie chuandong)
The crank-group driving mechanism is a kind of new transmission mechanism,it is mainly used in some special light industrial machinery.Based on the Newton- Raphson method,the kinematics characteristics of the crank-group driving mechanism’s structural unit is validated and calculated by using an example of MATLAB,the 3D modeling and dynamic simulation of the new mechanism is completed through SolidWorks and ANSYS,a reference for the further research and development of the mechanism is provided.